Ta’līm Mahārah al-Kitābah bistirātījiyyah PAILKEM bi al-Madrasah al-Ibtidā’iyyah al-Asy’ārī Sidorejo - Hasan, Laili Mas Ulliyah; Aziz, Muhammad Tareh (Study Program of Arabic Language Teaching, 2021)
The research problem are the students’ low writing skills in Arabic subjects and the teaching strategies used in the classroom. Hence, the researcher used the PAILKEM strategy with active learning and the Word Square model included in it. The PAILKEM strategy has been modified to become a strategic practice in improving the writing skills of Al-Asy'ari Elementary School pupils. With the PAILKEM strategy, the students become motivated to participate in lessons and the responsibility of the students is higher because the learning is grouped captivatingly but still takes care of the learning objectives that have been set. The results showed that after the PAILKEM strategy implementation, there were significant changes in students' learning, specifically in studying writing skills and developing students' social skills during the teaching process. The teaching activities were also effective.